Perancangan Foto Makanan Tradisional Kapurung Melalui Pendekatan Desain Afektif - Nofias Fajri; Firdhani Faujiyah; Nur Khaerani Busri (Jurnal Industri dan Teknologi Samawa, 2025)
The development of Industry 4.0 has brought a significant influence on Indonesian society to become all online. This causes food menus to be selected based on images, so that images become an important aspect in attracting consumer interest. In addition to changes in shopping styles and eating patterns, plus the trend of jungdood and emotional eating has had an impact on increasing Indonesia's obesity rate by 2 times. One of the solutions offered is to increase the consumption of healthy food. However, the fact is that photos of healthy foods trigger different responses when compared to foods high in fat and calories. So, a healthy food photo design is needed that gives the same effect as a photo of high-calorie high-fat food. This research focuses on the design of photos of traditional healthy food, namely kapurung to the photo design stage. Kansei engineering is used to find the characteristics and combinations of photos that consumers want. Then eye tracking determines the area of interest point on the photo object and the design combination. As well as factor analysis to determine the best kansei word representing traditional healthy food photos and couple comparisons to find the most preferred design. Based on the research conducted, the words kansei that represent the characteristics of healthy food photos according to respondents are "Creative", "Aesthetic", "Bright", "Fresh" and "Clear". In addition, the best photo in displaying the design according to respondents to display traditional healthy food photos is full styling with neutral presets